2008
DOI: 10.1016/j.jpeds.2008.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab Treatment of Intravenous Immunoglobulin–Resistant Kawasaki Disease

Abstract: Objective-To test the safety, tolerability, and pharmacokinetics of the anti-TNF-α monoclonal antibody, infliximab, in subjects with intravenous immunoglobulin (IVIG)-resistant Kawasaki disease (KD).Study design-We conducted a multicenter, randomized, prospective trial of second IVIG infusion (2 g/kg) versus infliximab (5 mg/kg) in 24 children with acute KD and fever following initial treatment with IVIG. Primary outcome measures were infliximab safety, tolerability, and pharmacokinetics. Secondary outcome mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
168
0
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 265 publications
(183 citation statements)
references
References 20 publications
6
168
0
9
Order By: Relevance
“…33 12 of these 48 patients had received infl iximab as part of a phase 1 multicentre, randomised, prospective trial of second intravenous immunoglobulin versus infl iximab for intravenous immunoglobulin-resistant Kawasaki disease. 8 This study showed that infl iximab was safe and well tolerated. Subsequently, a two-centre retrospective review of intravenous immunoglobulin-resistant patients treated with either a second intravenous immunoglobulin (n=86) or infl iximab (n=20) indicated that patients treated with infl iximab had fewer days of fever (median 8 vs 10 days, p=0·028) and shorter lengths of hospital syay (median 5·5 vs 6 days, p=0·04) than those given a second intravenous immunoglobulin.…”
Section: Systematic Reviewmentioning
confidence: 73%
See 2 more Smart Citations
“…33 12 of these 48 patients had received infl iximab as part of a phase 1 multicentre, randomised, prospective trial of second intravenous immunoglobulin versus infl iximab for intravenous immunoglobulin-resistant Kawasaki disease. 8 This study showed that infl iximab was safe and well tolerated. Subsequently, a two-centre retrospective review of intravenous immunoglobulin-resistant patients treated with either a second intravenous immunoglobulin (n=86) or infl iximab (n=20) indicated that patients treated with infl iximab had fewer days of fever (median 8 vs 10 days, p=0·028) and shorter lengths of hospital syay (median 5·5 vs 6 days, p=0·04) than those given a second intravenous immunoglobulin.…”
Section: Systematic Reviewmentioning
confidence: 73%
“…7,[28][29][30][31][32][33] A phase 1 trial of second intravenous immunoglobulin versus infl iximab for intravenous immunoglobulin-resistant Kawasaki disease showed that infl iximab was safe and well tolerated. 8 Subsequently, a retrospective review of intravenous immunoglobulin-resistant patients treated with either a second intravenous immunoglobulin or infl iximab showed that patients treated with infl iximab had fewer days of fever (median 8 vs 10 days, p=0·028) and shorter lengths of hospitalisation (median 5·5 vs 6 days, p=0·04) than those treated with a second intravenous immunoglobulin. 9 Interpretation Although the addition of infl iximab to primary treatment in acute Kawasaki disease did not reduce treatment resistance in this randomised clinical trial, infl iximab was shown to be safe and well tolerated, achieved a greater reduction in the left anterior descending coronary artery Z score, and reduced the number of days of fever, laboratory markers of infl ammation, and intravenous immunoglobulin reaction rates.…”
Section: Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In the future, by identifying a genetic signature for this group, more aggressive therapies, such as anticytokine therapy, plasmapheresis, or cyclosporin A, may be used to reduce the risk of coronary complications [70,86].…”
Section: Drug Name Antiplatelet Agents Dipyridamole [Persantine]mentioning
confidence: 99%
“…74,75 In accordance with this hypothesis, the usage of infliximab, the monoclonal antibody against TNF-a, has recently been found to be effective as a novel therapy for IVIG-resistant KD. [76][77][78] Thus, genes for cytokines including TNF-a could be candidates for KD susceptibility. However, consistent results have not been obtained.…”
Section: Candidate Gene Approachmentioning
confidence: 99%